Fit for work? Musculoskeletal disorders and the French labour market - McGee, Robin; Bevan, Stephen; Quadrello, Tatiana (London, 2009)
"This report looks at France in this wider global context and assesses where Romania is doing well and where it has challenges to confront. In addition, Appendix 3 compares Romania with other countries across a range of labour market, welfare and health care systems indicators."